PENERAPAN PROGRAM LITERASI DINI DALAM MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS PERMULAAN ANAK KELOMPOK B - Azka Safira; Fahruddin; Syaiful Musaddat; Ika Rachmayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of an early literacy program in improving the beginning reading and writing skills of children aged 5–6 years (Group B) at PAUD Rinjani, University of Mataram. Employing a qualitative research design with a descriptive approach, data were collected through observation, in-depth interviews with the classroom teacher and principal, and document analysis, including lesson plans and samples of student work. The data were analyzed using Miles’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the early literacy program, systematically implemented through activities such as read-aloud sessions, shared reading, letter and word games, and guided early writing exercises, significantly enhanced the children’s literacy skills. Notable improvements were observed in their ability to recognize letters, understand phonemes, read simple words and sentences, and write their own names and short texts. The success of the program was supported by several factors, including the teacher’s creativity in designing engaging and age-appropriate activities, the use of appealing visual media such as illustrated letter cards, parental involvement at home, and a stimulating and supportive classroom environment. Nevertheless, the implementation faced several challenges, particularly in addressing individual differences in children's developmental stages and the constraint of limited instructional time. Overall, the study underscores the importance of implementing structured and developmentally appropriate early literacy programs as a means to build foundational reading and writing skills that prepare young learners for formal education.